Myogenic differentiation of primary myoblasts and mesenchymal stromal cells under serum-free conditions on PCL-collagen I-nanoscaffolds - Arkudas, Andreas; Weigand, Annika; Beier, Justus; Horch, Raymund E.; Hardt, Moritz; Schneider, Paul; Schmid, Rafael; Lange, Claudia; Dippold, Dirk; Schubert, Dirk W.; Boos, Anja; Cai, Aijia (BMC Biotechnology, 2018)
The creation of functional skeletal muscle via tissue engineering holds great promise without sacrificing healthy donor tissue. Different cell types have been investigated regarding their myogenic differentiation potential under the influence of various media supplemented with growth factors. Yet, most cell cultures include the use of animal sera, which raises safety concerns and might lead to variances in results. Electrospun nanoscaffolds represent suitable matrices for tissue engineering of skeletal muscle, combining both biocompatibility and stability. We therefore aimed to develop a serum-free myogenic differentiation medium for the co-culture of primary myoblasts (Mb) and mesenchymal stromal cells derived from the bone marrow (BMSC) and adipose tissue (ADSC) on electrospun poly-ε-caprolacton (PCL)-collagen I-nanofiber
Keywords: Nanoscaffolds; Myogenic differentiation; Myoblasts; Mesenchymal stromal cells; Serum-free media; BMSC; Electrospun PCL-collagen I-nanofibers; ADSC